PENGEMBANGAN MODEL KEPUASAN KERJA UNTUK MENGHADAPI TURNOVER INTENTION KARYAWAN PADA PT KITADIN SITE EMBALUT (KALIMANTAN TIMUR) - Murfat Effendi (LPPM University 17 Agustus 1945 Samarinda, 2018)
This research purpose is to identify eand analyze development model of work satisfaction for facing turnover intention in PT. Kitadin Site Embalut (East Borneo). The Research formulation of problem are; 1. Do the performances of flow finance treasury system in region corporation Air MinumTirtakencanaSamarinda that used measurement liquidity ratio (treasury operation flow) in year 2015 up to 2017 experience an increase? 2. Is the performance of flow finance treasury in region corporation Air minum tirta kecana Samarinda that used measurement liquidity ratio (total debt) in year 2015 up to 2017 experience an increase? 3. Is the performance of flow finance treasury in region corporation Air Minum Tirta KencanaSamarinda that used measurement liquidity ratio (Spending Fund) in year 2015 up to 2017 experience an increase? 4. Does the performance of flow finance treasury in region corporation Air Minum Tirta Kencana Samarinda that used measurement flexibility ratio (Flow Treasury Clear and open) in year 2015 up to 2017 experience an increase?Basic Theory which author applied is Finance Accounting. Analystis insruments that author used are 1. Liquidity Ratio (Flow treasury operation). 2. Liquidity Ratio (Total debt). 3. Liquidity ratio (Spending Fund). 4. Flexibility Ratio (Clear and Open Treasury Flow. The hypothesis examined if the performance of finance treasury of region corporation air minum at samarinda experience an increase from year of 2015 up to 2017 so it comes to decision to accept the hypothesis and otherwise if the performances of finance treasury of region corporation air minum at samarinda experience a decrease from year 2015 up to 2017 the hypothesis will be decline.